PERAN KEPEMIMPINAN TERHADAP PENINGKATAN KINERJA PEGAWAI DI DINAS PERHUBUNGAN KOTA SAMARINDA - Tri Suhadi Yanto (ADMINISTRASI PUBLIK, 2018)
This study aims to determine toknow the role of Leadership on Employee Performance ImprovementAt  Department of Transportation in Samarinda City.            The result of the research shows that there is a positive and siginificant correlation between Leadership variable with Employee Performance at Department of Transportations in Samarinda City. Another thing can be known from the result of statistical test Koefisien Korelasi Product Moment the result is r = 0,696 which means there is a strong and positive relationship between the two variables.            Meanwhile, t test result ( table coefficients) obtained t value counted = 5,970  While the table statistics (ttabel) obtained from table t ( attached) for = 1,686 means t count > t table ( 5,970> 1,686 ). So it can be concluded that, the independent variable Leadership has a positive and sinificant relationship to Employee Perfomance. This it can be said also that the purpose of this study can be achieved, the problem can be solved and the hypothesis can be proven.